The Impact of Recession on the Distribution of Annual Unemployment - Beach, Charles M.; Kaliski, S. F. (Relations Industrielles / Industrial Relations, 1986)
The authors use microdata from the Canadian Annual Work Patterns Survey for 1978, 1980 and 1982 to compare the distributions of the annual unemployment experiences of persons.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Economic conditions; Economic depression; Economic impact; Labor Unions; Recessions; Statistical analysis; Studies; Unemployment